Discussion - Of Mr. Chance's Paper on A New Theory of the Genesis of Brown Hematite- Ores; and a New Source of Sulphur Supply (see p. 522) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1909)
Charles Catlett, Staunton, Va. (communication to the Secretary*):—Mr. Chance's suggestions that the brown hematite-ores of the Potsdam formation are due to the alteration in place of iron sulphide, and that their extension may reasonably he expected to contain valuable deposits of unaltered sulphide, are interesting; hut the facts marshaled by him are too limited